Marketing de contenidos en el reconocimiento de marca del restaurante Sorbetes N.A en la ciudad de Quevedo - Herrera Salazar, Jhoel Alberto (2023)
This degree work is centennial in the fast food restaurant Sorbetes N.A, which is located in the city of Quevedo, Los Rios province. This restaurant offers food and drinks on its menu, such as hamburgers, toasts and the star product sorbet. However, the restaurant faces multiple challenges such as low, almost zero, brand recognition among its potential customers and limited annual revenue growth, one of the most important factors being the inadequate management of its communication channels on certain digital platforms. To delve into this situation, an approach was applied with marketing strategies based on an exhaustive investigation of bibliographical sources and field studies. A methodology with a mixed approach of deductive and inductive methods was used, carrying out surveys and interviews in order to understand the interests of consumers and certain factors that influence the purchase decision.